Eco-friendly management of postharvest decay of Langra and Surjapuri mangoes (Journal of the Bangladesh Agricultural University, 2020)
Mahogani leaf extract, bishkatali leaf extract, garlic clove extract, brine solution and fruit washing were applied to investigate the efficacy for eco-friendly management of postharvest decay of Langra and Surjapuri varieties of mango. Chemical fungicide Bavistin (Carbendazim 50% WP), and non-treated control were used as positive and negative control treatments, respectively. Post-harvest decay caused by anthracnose and stem-end rot of mango were assessed. At 8th day of storage of Langra, lowest number of anthracnose spots were found in garlic clove extract followed by bishkatali. Significant reduction in anthracnose spots were observed in the treatments mahogani, fruit washing, Bavistin and brine solution, respectively. The lowest diseased area caused by anthracnose were found in Bavistin followed by garlic. The lowest number of stem-end rot lesions were found in mahogani followed by garlic and significantly reduced percentage of stem end rot lesions were observed in the treatments brine solution followed by Bavistin and bishkatali. In case of Surjapuri mango, the lowest number of anthracnose spots per fruit and disease area per fruit were obtained by garlic clove treatment. The lowest number of stem-end rot lesions was observed with bishkatali and mahogani leaf extracts, respectively and lowest stem-end rot diseased area per fruit was observed with garlic clove and mahogany leaf extracts, respectively. Overall higher number of anthracnose spot and stem-end-rot lesions per fruit was observed in control treatment. Garlic clove extract, bishkatali leaf extract and mahogani leaf extract were found effective in reducing post-harvest decay of mango.J Bangladesh Agril Univ 18(1): 34–39, 2020https://doi.org/10.5455/JBAU.94732